Evidence for subsidence in the 1989 Arctic winter stratosphere from airborne infrared composition measurements - Toon, G. C.; Farmer, C. B.; Schaper, P. W.; Lowes, L. L.; Norton, R. H.; Schoeberl, M. R.; Lait, L. R.; Newman, P. A. (1992)
Simultaneous measurements of the stratospheric burdens of CO2, HCN, N2O, CH4, OCS, CF2Cl2, CFCl3, CHF2Cl and HF were made by the Jet propulsion Laboratory MkIV interferometer on board the NASA DC-8 aircraft during January and early February 1989 as part of the Airborne Arctic Stratosphere Experiment. Data were acquired on 11 flights at altitudes of up to 12 km over a geographic region covering the NE Atlantic Ocean, Iceland and Greenland. The results obtained show large variations in the burdens of these tracers due to the effects of transport. The tropospheric source gas burdens were reduced inside the polar vortex, suggesting that the air had subsided with respect to the surrounding midlatitude air. Increased HF burdens inside the vortex support this interpretation. The results obtained from the different tracers are highly consistent with each other and indicate that in the 15- to 20-km altitude range inside the vortex, surfaces of constant volume mixing ratio were located some 5-6 km lower in absolute altitude than outside the vortex. The results also indicate that the magnitude of this subsidence increases with altitude. These conclusions are consistent with other measurements.